2012
DOI: 10.1002/nau.22242
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary dysfunction in male rats after bilateral neurectomy of the motor branch of the sacral plexus

Abstract: In male rats the perineal striated muscles are crucial to maintaining normal urinary continence, preventing retrograde ejaculation, and to expelling urine and seminal secretions. Bilateral neurectomy of the MBSP may not be appropriate for long term survival urinary studies because effects on urinary parameters can be contaminated and/or masked by impaired seminal fluid expulsion, as a consequence of impairment of striated urethral muscle function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…Nevertheless, our results suggest that the Bgm is relevant for both phases of the micturition because its blockade with lidocaine decreased of the ThP and caused episodes of saline dripping. Similar results have been reported in rats in which the transection of the motor branch of the pudendal nerve causes an increased number of small urine marks suggesting urinary incontinence . The voiding phase of micturition is also affected by the blocking of the Bgm activity by lidocaine, reducing the VV, and the MP.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, our results suggest that the Bgm is relevant for both phases of the micturition because its blockade with lidocaine decreased of the ThP and caused episodes of saline dripping. Similar results have been reported in rats in which the transection of the motor branch of the pudendal nerve causes an increased number of small urine marks suggesting urinary incontinence . The voiding phase of micturition is also affected by the blocking of the Bgm activity by lidocaine, reducing the VV, and the MP.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results have been reported in rats in which the transection of the motor branch of the pudendal nerve causes an increased number of small urine marks suggesting urinary incontinence. 24,25 The voiding phase of micturition is also affected by the blocking of the Bgm activity by lidocaine, reducing the VV, and the MP. Both variables are involved in the contractility of detrusor.…”
Section: Discussionmentioning
confidence: 99%
“…The female rats in this study demonstrated stereotyped behavior of micturition, similar to that described previously in male rats (24,25). The design of the top of the cage with the food and water container in the center of the jumbo cage VD (B) animals.…”
Section: 56)supporting
confidence: 77%
“…Micturition was recorded as previously described (24). The recordings took place in the last 6 h of dark and the first 6 h of light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation